The impact of community marketing on the food-online application during the pandemic in the region of Karawang West Java - Ignatius Septo Pramesworo; Tiolina Evi (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2023)
This study aims to analyze the effect of service quality, promotions, and customer satisfaction on customer loyalty of Gofood application users during the Covid-19 Pandemic at Perumnas Bumi Teluk Jambe Blok X Karawang, West Java. This research uses quantitative methods. The sample used was 109 respondents. Data analysis used multiple linear regression analysis which was processed using the SPSS version 25 application. The results showed that the multiple regression coefficients of service quality had no significant effect on customer loyalty, promotion had no significant effect on customer loyalty, customer satisfaction had a significant effect on customer loyalty and simultaneously a significant effect between service quality, customer satisfaction and promotion of customer loyalty.